Nesting success of corn buntings with respect to nesting habitat and other farmland characteristics - Yan, Clarice Pei Ling (Nanyang Technological University, 2023)
Nest site selection is a vital component of breeding success. Key features that influence nest site selection include concealment from predators and availability of food. Corn Bunting (Emberiza calandra) numbers have declined steeply in Britain, largely driven by agricultural intensification. Corn Buntings are ground-nesting farmland birds that breed late into the summer, making them vulnerable to nest losses due to crop harvests and agricultural practices. The aim of this study was to describe life histories of Corn Buntings and to identify key factors affecting the nest daily survival rates (DSR) of Corn Buntings during the breeding season. I examined 100 Corn Bunting territories in farmland in eastern Scotland during May 2022 to August 2022. Nest DSR and the influences of explanatory variables were estimated using RMark. Few nests were lost due to harvesting practices, indicating that other variables may be more crucial in affecting nest DSR. Nest stage, start day and their interaction were found to affect DSR significantly. The best-supported model predicted that DSR decreased with start day, especially during the chick stage although it was generally lower in the egg stage than in the chick stage. Crop cover, number of crops, mean crop height and altitude received little support in the models while the crop type nested in received no support in the models. Forage grass meadows during early summer and spring cereals in late summer could provide suitable nesting habitat throughout the entire breeding season, potentially boosting Corn Bunting nest DSR. Keywords: Nest site selection, farmland birds, nest survival, conservation, population monitoring